2018
DOI: 10.1016/j.aop.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Faddeev–Jackiw quantization of topological invariants: Euler and Pontryagin classes

Abstract: The symplectic analysis for the four dimensional Pontryagin and Euler invariants is performed within the Faddeev-Jackiw context. The Faddeev-Jackiw constraints and the generalized Faddeev-Jackiw brackets are reported; we show that in spite of the Pontryagin and Euler classes give rise the same equations of motion, its respective symplectic structures are different to each other. In addition, a quantum state that solves the Faddeev-Jackiw constraints is found, and we show that the quantum states for these invar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…In Refs. [49][50][51] another approach to the iterative symplectic algorithm can be found. In their approach, some columns of the pre-symplectic structure were ignored in the process of finding the zero-modes.…”
Section: Discussionmentioning
confidence: 99%
“…In Refs. [49][50][51] another approach to the iterative symplectic algorithm can be found. In their approach, some columns of the pre-symplectic structure were ignored in the process of finding the zero-modes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that the generalized brackets depend on , and this fact makes the P-CS theory different from Palatini theory. In fact, it is well known that two theories sharing the same equations of motion do not imply that these theories are equivalent at all [27][28][29]; the difference between the generalized brackets will be relevant in the quantization program; we need to remember that the symplectic structure is an essential ingredient in the quantum canonical approach [30]. It is important to note that the contribution of degrees of freedom just like the addition of matter fields could help us understand the nature of the parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the gauge transformations are an important part of the symmetries of the system because they characterize the core of a gauge theory. The identification of the gauge symmetries can be carry out by means different and powerful approaches such as the canonical framework developed by Dirac and Bergmann [1,2], the symplectic method of Faddeev-Jackiw [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and the Hamilton-Jacobi [HJ] procedure [19][20][21][22]. The HJ approach is an economical and elegant scheme for study gauge systems; it is based on the construction of a fundamental differential which has as principal components the HJ constraints called Hamiltonians, which can be involutives and noninvolutives.…”
Section: Introductionmentioning
confidence: 99%